COMMUNITY STRUCTURE OF MAKROZOOBENTHOS IN ESTUARY OF BANYUASIN RIVER OF SOUTH SUMATRA - Ni Komang Suryati; Eko Prianto (Pusbindiklat - LIPI, 2012)
Community structure of macrozoobentos in estuary of Banyuasin important as based of knowledge about bioindicator environtment. The aim of this research was to examine the community structure of macrozoobenthos in estuaries Banyuasin river of South Sumatra. This research conducted by field survey method. Field sampling was selected by purposive random sampling. Macrozoobenthos samples were taken using ekman grab. Further silt that is picked up from the tool was filtered using a filter to separate from the mud. Samples was inserted into the bottle sampel and then identifyed in the laboratory. Results showed that the highest density of macrozoobenthos occured in Oktober and the lowest in April. Diversity of macrozoobenthos based on index Shannon-Wiener average of all station showed a value of 1< H’ < 3. There were significant differences (P<0,05) at each sampling month and the highest value found in June amounting to 1,82. The value of uniformity during the research as seen from the difference in observation time was low. For environtmental quality criteria based on the diversity index Shannon-Wiener showed that the value of IML is 1,62 which means that in the area in the station that is contaminated with medium level.